Production and Utilization of Moodle-Based e-Learning to Enhance Higher-Order Thinking Skills with the STEM Approach - Restanti, Mida Ayu; Hasnunidah, Neni; Suyatna, Agus; Abdurrahman, Abdurrahman (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aimed to develop a Moodle-based e-learning platform with a valid, practical, and effective STEM approach to enhance Higher-Order Thinking Skills (HOTS). The research methodology employed for development purposes was the ADDIE model, consisting of five distinct phases: Analysis, Design, Development, Implementation, and Evaluation. The selection of research subjects for the field trial was conducted through cluster random sampling, wherein experimental and control classes were chosen. The experimental class utilized a Moodle-based e-learning solution for instructional purposes, while the control class adhered to traditional learning methods. Data were collected using validated questionnaires and written tests. The findings indicated that the Moodle-based e-learning products with a STEM approach are effective in enhancing students’ higher-order thinking skills. This was evident from the average n-Gain gain falling in the